Reprogramming Antagonizes the Oncogenicity of HOXA13-Long Noncoding RNA HOTTIP Axis in Gastric Cancer Cells. (23rd August 2017) - Wu, Deng-Chyang; Wang, Sophie S.W.; Liu, Chung-Jung; Wuputra, Kenly; Kato, Kohsuke; Lee, Yen-Liang; Lin, Ying-Chu; Tsai, Ming-Ho; Ku, Chia-Chen; Lin, Wen-Hsin; Wang, Shin-Wei; Kishikawa, Shotaro; et al.
Abstract : Reprogramming of cancer cells into induced pluripotent stem cells (iPSCs) is a compelling idea for inhibiting oncogenesis, especially through modulation of homeobox proteins in this reprogramming process. We examined the role of various long noncoding RNAs (lncRNAs)-homeobox protein HOXA13 axis on the switching of the oncogenic function of bone morphogenetic protein 7 (BMP7), which is significantly lost in the gastric cancer cell derived iPS-like cells (iPSLCs). BMP7 promoter activation occurred through the corecruitment of HOXA13, mixed-lineage leukemia 1 lysine N-methyltransferase, WD repeat-containing protein 5, and lncRNA HoxA transcript at the distal tip (HOTTIP) to commit the epigenetic changes to the trimethylation of lysine 4 on histone H3 in cancer cells. By contrast, HOXA13 inhibited BMP7 expression in iPSLCs via the corecruitment of HOXA13, enhancer of zeste homolog 2, Jumonji and AT rich interactive domain 2, and lncRNA HoxA transcript antisense RNA (HOTAIR) to various cis -element of the BMP7 promoter. Knockdown experiments demonstrated that HOTTIP contributed positively, but HOTAIR regulated negatively to HOXA13-mediated BMP7 expression in cancer cells and iPSLCs, respectively. These findings indicate that the recruitment of HOXA13–HOTTIP and HOXA13–HOTAIR to different sites in the BMP7 promoter is crucial for the oncogenic fate of human gastric cells. Reprogramming with octamer-binding protein 4 and Jun dimerization protein 2 can inhibit tumorigenesis by switching off BMP7.